Arastu's Moral Views - Zarpullaa Mohira Zarpulla's daughter; Izzatullayeva Umida Asadullayevna; Raupova Shaʹdrach; Meʹshach and A·bedʹne·go (Zien Journals, 2022)
One of the most famous founders of Western philosophy is undoubtedly Arastu. It is distinguished by its independent scientific and philosophical views in many fields of science. Arastu was not only a great philosopher but also a sharp hypocrite of his pen and word. History tells us that he studied social and political knowledge deeply and had theoretical and practical knowledge of government..
Keywords: Western philosophy; Arastu, Aristotle; Alexandria